2017
DOI: 10.3174/ajnr.a5066
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Lactate Content and Amide Proton Transfer Values in the Basal Ganglia of a Neonatal Piglet Hypoxic-Ischemic Brain Injury Model Using MRI

Abstract: BACKGROUND AND PURPOSE:As amide proton transfer imaging is sensitive to protein content and intracellular pH, it has been widely used in the nervous system, including brain tumors and stroke. This work aimed to measure the lactate content and amide proton transfer values in the basal ganglia of a neonatal piglet hypoxic-ischemic brain injury model by using MR spectroscopy and amide proton transfer imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…In particular, the time of normalization of plasma lactate in cooled HIE babies showed a 23.1 h median value (range 2.9–73.5 h) in babies with good outcome and a 39.1 h median value (range 8.1–134.1 h) in the ones who survived with a poor outcome [ 39 ]. Moreover, a recent MR spectroscopy imaging study performed in a neonatal piglets hypoxic-ischemic brain injury model showed that, after the hypoxic-ischemic insult, the basal ganglia lactate content increase immediately, it reaches its maximum value at 2–6 hours, and then gradually decreases to the level of the control group [ 40 ]. In our sample, although all the babies were diagnosed with HIE Sarnat II-III and fulfil the criteria adopted from the Italian Recommendations for TH, urinary lactate relative concentration in HIE surviving newborns showed a similar trend over time whenever compared with healthy newborns, suggesting the existence of a wide variability either in the causes of HIE or in individual responses to hypoxic-ischemic insult.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the time of normalization of plasma lactate in cooled HIE babies showed a 23.1 h median value (range 2.9–73.5 h) in babies with good outcome and a 39.1 h median value (range 8.1–134.1 h) in the ones who survived with a poor outcome [ 39 ]. Moreover, a recent MR spectroscopy imaging study performed in a neonatal piglets hypoxic-ischemic brain injury model showed that, after the hypoxic-ischemic insult, the basal ganglia lactate content increase immediately, it reaches its maximum value at 2–6 hours, and then gradually decreases to the level of the control group [ 40 ]. In our sample, although all the babies were diagnosed with HIE Sarnat II-III and fulfil the criteria adopted from the Italian Recommendations for TH, urinary lactate relative concentration in HIE surviving newborns showed a similar trend over time whenever compared with healthy newborns, suggesting the existence of a wide variability either in the causes of HIE or in individual responses to hypoxic-ischemic insult.…”
Section: Discussionmentioning
confidence: 99%
“…Under this circumstance, lactate would, thus, be a less reliable predictive marker in the era of TH, unlike it used to be in untreated newborns. Moreover, a recent animal study has reported that the lactate content would become maximal at 2–6 h after the hypoxic-ischemic insult and then gradually decreased to the level of the control group even in normothermic models ( 28 ). Considering the time window and the duration of TH, it is probable that the relative concentration of lactate would not be sufficiently prognostic when performing 1 H-MRS scans.…”
Section: Discussionmentioning
confidence: 99%
“…17 In the current study, the regulation mechanism of lactate and glucose after HI was investigated on the basis of the ANLS hypothesis. A high concentration of lactate or hypoxia can induce activation of glycolytic enzymes 18,19 and further upregulate MCTs. Immunohistochemical analyses showed that after HI, the expression levels of MCT-2 and MCT-4 also increased, peaked around 12-24 hours, and then decreased.…”
Section: Discussionmentioning
confidence: 99%